Sociodemographic, Clinical, and Psychosocial Characteristics of People with Hemophilia in Portugal: Findings from the First National Survey - Pinto, Patrícia Ribeiro; Paredes, Ana Cristina; Pedras, Susana; Costa, Patrício; Crato, Miguel; Fernandes, Susana; Lopes, Manuela; Carvalho, Manuela; Almeida, Armando (TH Open, 2018)
Hemophilia is a rare genetic bleeding disorder associated with pain, impaired functionality, and decreased quality of life (QoL). Several studies have focused on patient-reported outcomes of people with hemophilia (PWH) worldwide, but no such data are available for Portugal. This survey aimed to describe sociodemographic, clinical, and psychosocial characteristics of PWH of all ages in Portugal. Questionnaires were answered by self-report or by parents of children with hemophilia (proxy version). Variables assessed were sociodemographic and clinical, physical activity patterns, pain, functionality (HAL/PedHAL), QoL (A36 Hemofilia-QoL/CHO-KLAT), anxiety and depression (PROMIS), and illness perceptions (IPQ-R). One-hundred and forty-six PWH answered the survey: 106 adults, 21 children/teenagers between 10 and 17 years, 11 children between 6 and 9 years, and 8 children between 1 and 5 years. Most participants had severe hemophilia (60.3%) and type A was most commonly reported (86.3%). Bleeding episodes, joint deterioration, and pain were very prevalent, with the ankles and knees being the most affected joints, as illustrated by HAL/PedHAL scores. The A36 Hemofilia-QoL assessment showed moderate QoL (96.45; 0–144 scale) and significant anxiety and depression symptoms were found in 36.7 and 27.2% of adults, respectively. CHO-KLAT global score (0–100 scale) was 75.63/76.32 (self-report/proxy). Concerning hemophilia-related illness beliefs, a perception of chronicity and symptoms unpredictability was particularly prominent among adults and children/teenagers. This survey provided a comprehensive characterization of Portuguese PWH, including the first report of psychosocial characteristics. The findings allow for a deeper understanding of life with hemophilia in Portugal and the identification of relevant health care and research needs.
Keywords: hemophilia; pain; quality of life; functionality; psychological factors